Control of coal separation in a jig using a radiometric meter. (September 2016) - Cierpisz, S.; Kryca, M.; Sobierajski, W.
Highlights: A radiometric density meter can be applied effectively to control a jig operation. A monitor of the natural radiation from the bed can control a jig operation. These methods give better results of a jig control than the conventional float. The natural radiation method is cheaper and does not require a radiation source. Abstract: A new monitoring system based on the monitoring of natural radiation emitted by the material in the separation zone of a jig compartment has been developed and tested in parallel with a radiometric density meter and a conventional float. The authors investigated the correlation between the separation density monitored by the meter and the intensity of the natural radiation. The correlation coefficient was ca. R = 0.973 and the standard deviation of the measurement in regression with the density meter indications was sc = 0.034 g/cm 3 . This shows that after a float as the measuring unit in a control system is replaced by a natural radiation monitor, one can expect good stabilisation of the separation density. The paper discusses advantages of such systems over float-based systems.